2021
DOI: 10.1111/clr.13822
|View full text |Cite
|
Sign up to set email alerts
|

Osseointegrated implant survival, success and prosthodontic outcomes in composite free flaps: A 10‐year retrospective cohort study

Abstract: The surgical treatment of cancer involving the maxillofacial region results in significant morbidity and reduces the health-related quality of life of patients (Barrios et al., 2015;Kamstra et al., 2011). The development of surgical techniques in recent decades has resulted in the use of composite free flaps as the ideal choice for reconstruction of large segments of the maxilla and mandible (Batstone, 2018).Composite free flaps restore facial structure, improve airway function, speech, deglutition, masticatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…The systematic review encompassed 18 studies, with 17 being retrospective [ 12 14 , 16 28 , 30 ] and one prospective cohort study [ 29 ]. In total, 774 patients (445 males, 252 females, and 77 unreported) were involved, and 1988 dental implants were used in free fibula grafts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The systematic review encompassed 18 studies, with 17 being retrospective [ 12 14 , 16 28 , 30 ] and one prospective cohort study [ 29 ]. In total, 774 patients (445 males, 252 females, and 77 unreported) were involved, and 1988 dental implants were used in free fibula grafts.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies focused solely on mandibular defects [ 18 , 19 , 23 , 26 , 27 , 29 ], while the others examined both maxillary and mandibular resections. Additionally, four studies assessed implants placed in natural bones [ 12 , 21 , 25 , 26 ], and three studies compared implant success rates across different graft types [ 14 , 20 , 30 ], such as scapula, DCIA, and MFC, alongside free fibular grafts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors largely highlight that peri-implantitis is directly related to inability to perform proper oral hygiene procedures [ 22 ]. Plus, patients who underwent reconstructive surgery suffer from limitations in oral opening because of oral vestibule contracture, reporting difficulty in accessing the abutments for effective home-care oral hygiene procedures [ 23 ]. As many studies demonstrated that higher plaque levels [ 24 , 25 ] and lack of accessibility for cleaning at implant level [ 21 ] are both significantly associated with peri-implantitis, oral hygiene performed by patients therefore represents a key component in preventing peri-implant diseases [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the dental rehabilitation of the reconstructed bone, a dental implant was mainly used. Implant success was defined as an implant being comfortable to the patient and functionally supporting a prosthesis [7]. Primary implant stability is the most important feature for implant survival and success during implant installation.…”
Section: Introductionmentioning
confidence: 99%